2011
DOI: 10.4244/eijv7ska11
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of bifurcation lesions with a drug-eluting balloon: the PEPCAD V (Paclitaxel Eluting PTCA Balloon in Coronary Artery Disease) trial

Abstract: Percutaneous treatment of bifurcation lesions with a drug-eluting balloon resulted in a procedural success of 100%. Follow-up angiography at nine months showed DES-like results in MB and SB. However, when the DEB was used in combination with a BMS (MB), the possibility of late stent thrombosis cannot be ruled out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(83 citation statements)
references
References 9 publications
0
79
0
1
Order By: Relevance
“…Therefore, DEB without stent treatment mostly focuses on high-risk restenotic lesions, such as small vessels, bifurcations, or ISR [4]. Several clinical trials have confirmed the safety of paclitaxel-coated balloon in patients with de novo lesions in small coronary arteries or in bifurcation lesions [12,13,23,24,25,26,27,28]. However, information on DEB treatment of non-small coronary artery lesions is limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, DEB without stent treatment mostly focuses on high-risk restenotic lesions, such as small vessels, bifurcations, or ISR [4]. Several clinical trials have confirmed the safety of paclitaxel-coated balloon in patients with de novo lesions in small coronary arteries or in bifurcation lesions [12,13,23,24,25,26,27,28]. However, information on DEB treatment of non-small coronary artery lesions is limited.…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical information on the efficacy and safety in de novo coronary lesions is limited. Moreover, several studies and trials have produced conflicting results in patients with a stable coronary artery disease [8,9,10,11,12,13]. Therefore, we hypothesize that DEB may also be safe for the treatment of non-small coronary artery lesions.…”
Section: Introductionmentioning
confidence: 99%
“…The data from literature on DEB in this indication is very sparse. In PEPCAD V study 11 on a small number of 28 patients with bifurcation lesion first a dilatation with DEB of both the major and the side branches was performed, and following this BMS was implanted into the main branch with the stent opening towards the side branch with one balloon. Angiography results after 9 months have shown slight late lumen loss in side branches treated mostly with DEB without the stent implantation, and in 3 patients after 6, 8 and 10 months a late and very late thrombosis of the BMS implanted into the main branch was recorded.…”
Section: Raspravamentioning
confidence: 99%
“…Over the last several years, we have seen a wide variety of clinical trial designs including lesion sub-sets (i.e., bifurcations, de novo lesions and STEMI) [4,5] (P. Stella, Results of the DEB AMI trial, TCT 2011, Washington DC, US), that have not been sufficiently studied at the experimental setting [1]. Some of these studies, usually small and not properly controlled, have yielded confusing efficacy and safety results thus tainting the clinical potential of this technology.…”
mentioning
confidence: 99%